Effects of Rhodiola Rosea Supplementation on Exercise and Sport: A Systematic Review - Lu, Yao; Deng, Bin; Xu, Luhua; Liu, Hanjiao; Song, Yinzhi; Lin, Fengxia (Frontiers in Nutrition, 2022)
Rhodiola rosea (Golden Root Extract; RR) is an herbaceous perennial, which is native to in high altitude areas, such as Tibet in western China. It has been studied for its positive pharmacological effects on health. However, only a handful of studies have evaluated the effects of RR as an exercise supplement for sport and physical activity. The aim of this study was to evaluate whether Rhodiola can be used as a supplement to improve human exercise ability. Studies were reviewed in accordance with the PRISMA guidelines and conducted between August and November, 2021. Databases searched included CNKI, Wanfang, VIP, CBM, Cochrane, Embase, Web of Science, and PubMed. Related terms were combined with keywords and MeSH subject headings using the corresponding Boolean operators: Rhodiola rosea, arctic root, roseroot, golden root, hongjingtian, and sports and exercise. A total of 11 papers were reviewed. Most of the studies reported that RR supplementation has a positive effect on athletic ability and sports performance, and no obvious adverse reactions were reported. Subjects taking RR showed a reduction in pain and muscle damage after exercise training, improved skeletal muscle damage, enhanced antioxidant capacity thereby reducing oxidative stress, reduced RPE scores, and improved athletic explosive power, but did not reduce the rating of perceived exertion (RPE) scores. RR appears to act as a safe and effective supplementation for sport and exercise.